INTERNALISASI AKIDAH ISLAM DALAM PEMBENTUKAN KARAKTER MUSLIM KONTEMPORE - Rasyidah; Eka Putra Wirman; Hasnah (As-Sulthan Journal of Education, 2026)
This study examines the internalization of Islamic creed (aqidah) values in shaping the character of contemporary Muslims. Aqidah serves as the fundamental foundation that directs Muslims’ beliefs, attitudes, and moral behavior. This article aims to analyze how the core values of Islamic creed—particularly tauhid, iman, kufr, and nifaq—are internalized and function as moral guidance in the context of modern life. This research employs a qualitative library research method by analyzing classical and contemporary Islamic literature, the Qur’an, and prophetic traditions (hadith). The findings reveal that the internalization of aqidah values strengthens spiritual awareness, moral integrity, and consistency between belief and action among Muslims. Moreover, a proper understanding of aqidah plays a strategic role in protecting individuals from moral degradation and ideological challenges emerging in the modern era. Therefore, strengthening the internalization of Islamic creed values is essential to develop Muslim character that is faithful, ethical, and resilient in facing contemporary social challenges.